2000
DOI: 10.2527/2000.7871885x
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase responses of pigs challenged orally with Salmonella typhimurium.

Abstract: This study evaluated responses of the systemic endocrine stress (cortisol) and growth (IGF-I, GH) axes, as well as those of inflammatory mediators (prostaglandin E2 [PGE2] and tumor necrosis factor alpha [TNFalpha]), to active infection with Salmonella typhimurium. Eighteen crossbred barrows were penned individually with ad libitum access to feed and water. After an acclimation period, jugular catheters were placed in all animals. Control pigs received sterile broth orally (CON, n = 7), whereas the treated pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
66
3
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 29 publications
18
66
3
5
Order By: Relevance
“…Our results revealed that oral exposure to S. Typhimurium and S. Enteritidis led to an~10% reduction in growth, which was likely explained by a reduction in feed intake (4% by S. Typhimurium group and 11% by S. Enteritidis group) as the level of feed intake is a basic and important factor that determines the rate of growth and body composition achieved by animals during their lifecycles (Richards, 2003). This observation is in agreement with those of previous studies by Balaji et al (2000), Turner et al (2002) and Burkey et al (2004) who reported lower feed intake and growth rate in pigs orally challenged with S. Typhimurium. However, to the best of our knowledge, no other studies of the effect of oral infection with S. Enteritidis on the growth performance of pigs have been conducted to date.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results revealed that oral exposure to S. Typhimurium and S. Enteritidis led to an~10% reduction in growth, which was likely explained by a reduction in feed intake (4% by S. Typhimurium group and 11% by S. Enteritidis group) as the level of feed intake is a basic and important factor that determines the rate of growth and body composition achieved by animals during their lifecycles (Richards, 2003). This observation is in agreement with those of previous studies by Balaji et al (2000), Turner et al (2002) and Burkey et al (2004) who reported lower feed intake and growth rate in pigs orally challenged with S. Typhimurium. However, to the best of our knowledge, no other studies of the effect of oral infection with S. Enteritidis on the growth performance of pigs have been conducted to date.…”
Section: Discussionsupporting
confidence: 92%
“…We did not observe any changes in body temperature of the infected pigs, which was supported by the results reported by Rostagno et al (2011), who concluded that infection with S. Typhimurium did not lead to development of any clinical symptoms in finishing pigs. In contrast, Balaji et al (2000) reported higher body temperature in weaned pigs orally infected with 3 × 10 9 cfu S. Typhimurium. A possible explanation for this may be that infection with very large numbers of Salmonella is required to initiate clinical disease (i.e.…”
Section: Discussionmentioning
confidence: 79%
“…In swine, oral infection by Salmonella enterica serovar Typhimurium (hereafter referred to as Typhimurium) results in growth suppression and an array of associated physiological effects (Schwartz, Oral inoculation with Salmonella enterica serovar Typhimurium or Choleraesuis promotes divergent responses in the somatotropic growth axis of swine Balaji et al, 2000;Jenkins et al, 2004). Infection by Salmonella enterica serovar Choleraesuis (hereafter referred to as Choleraesuis), another important swine pathogen, is more likely to cause septicemia in growing pigs (Schwartz, 1999), but little has been reported comparing these 2 serovars in terms of their effects on key regulatory elements of the endocrine growth axis.…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible explanations could be its very fast turnover as described by Jesmock et al [11] in E. coli-infected pigs. Balaji et al [4] found increased serum TNF-α levels in pigs 6 h and later after inoculation of ST. However, the lack of plasma TNF-α was described in septicemic calves [23], mice [14] and weaned pigs infected with ST [25].…”
Section: Discussionmentioning
confidence: 98%